2013
DOI: 10.1542/peds.2013-2656
|View full text |Cite
|
Sign up to set email alerts
|

Children, Adolescents, and the Media

Abstract: Media, from television to the “new media” (including cell phones, iPads, and social media), are a dominant force in children’s lives. Although television is still the predominant medium for children and adolescents, new technologies are increasingly popular. The American Academy of Pediatrics continues to be concerned by evidence about the potential harmful effects of media messages and images; however, important positive and prosocial effects of media use should also be recognized. Pediatricians are encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
189
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 653 publications
(217 citation statements)
references
References 20 publications
2
189
3
8
Order By: Relevance
“…Future studies should aim at incorporating objectively measured physical activity (i.e., by accelerometry and direct observation) in order to obtain more information about time spent in different activity levels and physical activity behaviors across the whole day. Finally, data on sedentary behaviors and physical activity behaviors were dichotomized according to current guidelines and recommendations [6,22-25]. This may have potentially led to a loss of information and statistical power to detect associations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should aim at incorporating objectively measured physical activity (i.e., by accelerometry and direct observation) in order to obtain more information about time spent in different activity levels and physical activity behaviors across the whole day. Finally, data on sedentary behaviors and physical activity behaviors were dichotomized according to current guidelines and recommendations [6,22-25]. This may have potentially led to a loss of information and statistical power to detect associations.…”
Section: Discussionmentioning
confidence: 99%
“…These variables were combined to estimate daily television viewing by using the following formula: daily use = {[(days per week) * (hours on a weekday)] + [(days per weekend) * (hours on a weekend day)]}/7. Average daily television viewing was then dichotomized into ≥2 hours/day versus <2 hours/day, based on current recommendations on screen-based entertainment for young children [6,21,22]. Average daily computer game use was dichotomized into ≥1 hour/day versus <1 hour/day, since only a small percent of children used the computer (games) for 1 or more hours per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Academy of Pediatrics (AAP) 24 policy statement on children, adolescents, and the media proposes a guideline to limit total media time (including new media such as cell phones, tablets, and social media) to no more than 2 h/d. 20 and a more recent school-based study 14 described earlier were considered during grade assignment for this indicator.…”
Section: Sedentary Behaviors: C-mentioning
confidence: 99%
“…The WHO Global Health Observatory 26 reported age-standardized estimates for the proportion of adults achieving the adult PA recommendations as 61.6% of adults, 67.8% of males, and 55.4% of females. The UAE Indoor Air, Health, and Nutrition Study 6 used the short form International Physical Activity Questionnaire 27 reported that 41.2% of the adult Emirati females (N = 478) achieved the PA recommendations 24 with a lower proportion in urban areas (37.1%) compared with rural areas (47.8%). The study reported an inverted-u shape for the proportion of adult Emirati females achieving the recommended PA levels by quintile (Q) of wealth index (incorporating household income, assets, housing type, and household size): Q1 (poorest 20%) 26.5%; Q2 54.0%; Q3 50.6%; Q4 51.0%; and Q5 (wealthiest 20%) 23.2%).…”
Section: Family and Peers: C-mentioning
confidence: 99%